Návrh vybraných uzlů malokapacitní extruzní linky - Nečesal, Filip (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Tato diplomová práce se zabývá návrhem, výrobou a testováním nízkokapacitní extruzní linky určené pro produkci filamentu vhodného pro použití ve FDM tiskárnách. V úvodní části práce je prezentován současný stav poznání v oblasti technologií výroby filamentu, včetně přehledu stávajících průmyslových i menších výrobních systémů, jejich výhod a limitací. Hlavní část práce se věnuje konstrukčnímu návrhu vybraných uzlů tohoto zařízení, s cílem vytvořit efektivní, kompaktní a funkční zařízení, které splňuje požadavky na nízkou produkční kapacitu. V experimentální části je extruzní linka podrobena testování za účelem ověření technických parametrů a vlastností nezbytných pro správnou funkčnost celého systému. Na základě experimentální části práce jsou v závěru práce formulována doporučení pro technickou praxi a případné možnosti optimalizace pro budoucí vývoj této technologie.

This thesis deals with the design, production and testing of a low-capacity extrusion line for the production of filament suitable for use in FDM printers. In the introductory part of the thesis, the current state of knowledge in the field of filament production technology is presented, including a review of existing industrial and small-scale production systems, their advantages and limitations. The main part of the thesis is devoted to the design of selected nodes of this equipment, with the aim of creating an efficient, compact and functional device that meets the requirements for low production capacity. In the experimental part, the extrusion line is tested in order to verify the technical parameters and characteristics necessary for the correct functionality of the whole system. Based on the experimental part of the work, recommendations for technical practice and possible optimization options for future development of this technology are formulated in the conclusion of the work.
Design of selected nodes of a small-capacity extrusion line
Keywords: Nízkokapacitní extruzní linka; Výroba filamentu; Aditivní výroba; FDM tisk; Polymerní extruze; Arduino; Low-capacity extrusion line; Filament production; Additive manufacturing; FDM printing; Polymer extrusion; Arduino